Differences in Sociodemographic Characteristics of Schizophrenia Patients between Rural and Urban Areas in Badung Regency - Setiawati, Ni Made (WMJ (Warmadewa Medical Journal), 2020)
Several studies have found differences in the incidence of schizophrenia in rural and urban areas. Most of the studies found that schizophrenia incidence was higher in urban areas. The purpose of this study was to determine differences in sociodemographic characteristics of schizophrenic patients according to rural or urban conditions in their homes. An observational, cross-sectional analytic, study conducted. The sample in this study were 503 people who had been diagnosed with schizophrenia recorded at community health centres in Badung Regency until October 2019. Sociodemographic data of patients were observed and then grouped according to the residence of rural or urban patients. Chi-square test with a significant value of P <0.005 used to analyze the result. The proportion of schizophrenia is higher in urban than in rural areas (61.1%: 38.9%). There are differences in the incidence of men and women in villages and cities (p = 0.011), differences in rural and educational events low whereas in urban areas on the contrary (P <0.0001). More schizophrenic patients do not work and live in cities than in villages (p = 0.002) and that people who are not married and live in cities suffer more schizophrenia (p = 0.014), only the age group variable was no difference (p = 0.14). The incidence of schizophrenia is higher in urban areas with differences in characteristics found in variables of gender, education level, employment status and marital status. Thus, can be an input to the health department and staff so that psychological education and screening are more directed at urban communities. Keywords: Schizophrenia, rural, urban sociodemography